KERAGAMAN BIOPELET LIMBAH TANAMAN PADI (Oryza sativa sp) SEBAGAI ENERGI ALTERNATIF RAMAH LINGKUNGAN - GA, Praptiningsih; Nuriana, Wahidin (JURNAL AGRI-TEK, 2014)
The abundance of rice straw and rice husks in Indonesia is a potential source of biomass that can be converted into biomass pellet (biopellets).. Pelletization can improve the quality and burning characteristic of the biomass. Bio-pellet is an alternative energy that can substituted low grade coal from biomass sources. The purpose of this study is to improve the quality of biopellets. Pellet made with some variation of the biomassa. Biopellet consists of a mixture of the rice straw and husks, the rice straw and bran, the rice husks and bran with a ratio of 1 : 1. The test of biopellet included moisture content, volatile matters, ash, substances, fixed carbon, and calorific value. The results showed a mixed type of biomassa affects the characteristics biopellet. Based on the physic chemical properties, biopellet of the husk+bran mixture and the rice straw + bran have better quality than other biopellet. The biopellet of husk +bran has 4138 kcal/kg of calorific value. The biopellet of the straw+bran have the lowest consumption rate that is 0.60 kg/h. Additionally, the biopellet of the straw+bran has 3223 kcal/kg of calorific value.Keywords : straw, biomass, biopellet, alternative energy